2008
DOI: 10.2174/187152808784165199
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a multifactorial disease characterized by chronic inflammation of the joints. Both genetic and environmental factors are involved in the pathogenesis of joint destruction and disability. In the inflamed RA joint, the synovium is highly infiltrated by CD4+ T cells, B cells, and macrophages. Furthermore, the intimal lining becomes hyperplastic due to the increased numbers of macrophage-like and fibroblast-like synoviocytes. This hyperplastic intimal synovial lining forms an aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 0 publications
1
39
0
5
Order By: Relevance
“…Circulating IL-8, on the other hand, has previously been detected only in SCD patients when in crisis or presenting acute syndrome [16 -19]; the current availability of more sensitive detection tools, however, probably explains this discrepancy. A role for TNF-␣, an important proinflammatory cytokine, has been appointed in a number of inflammatory diseases that include sepsis, rheumatoid arthritis, and Chrohn's disease, where this molecule appears to participate in up-regulating the cytokine cascades responsible for inflammation [20,21]. IL-8 (CXCL8) is a key mediator in neutrophil-mediated acute inflammation, with a crucial role in a number of chronic inflammatory diseases and lung pathologies [22].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating IL-8, on the other hand, has previously been detected only in SCD patients when in crisis or presenting acute syndrome [16 -19]; the current availability of more sensitive detection tools, however, probably explains this discrepancy. A role for TNF-␣, an important proinflammatory cytokine, has been appointed in a number of inflammatory diseases that include sepsis, rheumatoid arthritis, and Chrohn's disease, where this molecule appears to participate in up-regulating the cytokine cascades responsible for inflammation [20,21]. IL-8 (CXCL8) is a key mediator in neutrophil-mediated acute inflammation, with a crucial role in a number of chronic inflammatory diseases and lung pathologies [22].…”
Section: Discussionmentioning
confidence: 99%
“…SAA has been shown to bind to a variety of receptors including the formyl peptide-receptor like-1 receptor (80,81), Tanis (82), CD36 and lysosomal integral membrane protein-II analogous-1 (83), the receptor for advanced glycation end products (84,85), ␣IIb␤3 integrin (86), and the scavenger receptor BI (87,88). More recently, it was suggested that SAA-induced nitric oxide production by macrophages is Toll-like receptor (TLR) 4-dependent (89).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence generated in both animal models and in human studies support the role of TNF-␣, IL-1, and IL-6 in the pathogenesis of RA (Dayer et al, 2001;Scott and Kingsley, 2006;Hennigan and Kavanaugh, 2008). Treatment with Remicade, Humira, Enbrel, Kineret, and Tocilizumab reduce joint pain and swelling, and retard progression of bone loss in patients whose disease is unsatisfactorily controlled by conventional disease-modifying antirheumatic drugs (Okamoto et al, 2008). However, these biologic agents are limited due to the requirement for parenteral administration, difficulty in dose titration, poor reversibility, induction of host neutralizing antibody response, high production costs, and a significant population of patient refractory to the treatment.…”
mentioning
confidence: 99%